Infrared thermography applied to the evaluation of metabolic heat loss of chicks fed with different energy densities - Ferreira, V. M O S (2011)
Brazil must comply with international quality standards and animal welfare requirements in order to maintain its position as world's largest exporter of poultry meat. With the scenario of global climate change there is the forecast of occurrence of extreme events with characteristics of both excess cold and heat for several regions of the country. This study aimed to evaluate the effectiveness of using images of infrared thermography to evaluate the loss of sensible heat in young broilers fed different dietary energy levels. Twenty birds were reared in a house with appropriate brooding using infrared lamps. Birds were distributed in a completely randomized experimental into two treatments: T1 (control diet with 2950 kcal ME/kg -1), and T2 (high-energy diet with 3950 kcal ME/kg -1). Infrared thermographic images of the birds were recorded for four consecutive days. One bird was randomly chosen per treatment, and had special images taken and analyzed. Average surface temperature of the body area was calculated using the surface temperature recorded at 100 spots (50 at the front and 50 at the lateral side of the bird's body). Mean surface temperature of the flock was calculated recording 100 spots on the group of birds. Total radiant heat loss was calculated based on the average data of surface temperature. The results indicated that the young broilers fed the high-energy diet presented a metabolic energy loss equivalent to 0.64 kcal h -1, while the birds fed with the control diet lost 2.18 kcal h -1. This finding confirms that oil supplementation to the diet reduces bird heat loss. The infrared camera was able to record young broilers' surface temperature variation when birds were fed diets with different energy contents.